2002
DOI: 10.1080/01443610120113283
|View full text |Cite
|
Sign up to set email alerts
|

A clinico-epidemiological review of cervical cerclage from the Assir region of Saudi Arabia

Abstract: A retrospective review was conducted on patients who had cervical cerclage performed because of suspected cervical incompetence over a 7-year period to assess the outcome of pregnancy and complications resulting from the cerclage. Other factors that could affect the outcome and complications were also assessed. Out of 196 patients who had the operation, 154 patients had adequate records available and therefore comprised the study population. There were 139 (90%) live births of which 76.6% weighed more than 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…Previous studies have reported a wide range of pregnancy outcomes. Sobande reported 90% live births while Jogen reported 43% live births [24,25]. Findings in this study are also closely related to a study in Zambia with 76.8%, 14% and 9.2% of term, pre-term and miscarriages respectively [26].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have reported a wide range of pregnancy outcomes. Sobande reported 90% live births while Jogen reported 43% live births [24,25]. Findings in this study are also closely related to a study in Zambia with 76.8%, 14% and 9.2% of term, pre-term and miscarriages respectively [26].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the post cerclage survival rate of babies was 81%. This is comparable to that shown by Bukahri (27) but less than 90% shown by Sobande 43 , 87% by Harger (30) and by Kurup (75), which was 85%. In this study, 77% of babies had a birth weight of more than 2000g which is almost equal to that showed by Sobande which was 76.6%.…”
Section: Discussionsupporting
confidence: 80%
“…3 Remote sequelae and genitourinary injury because of cerclage placement are rare. 4 Genitourinary fistula formation can complicate any pelvic surgery. Approximately 80% of vesicovaginal fistulas in the developed world are secondary to benign gynecologic surgery.…”
mentioning
confidence: 99%